Economic Drivers in Sustainable Innovation: The Impact of Cost and Process Selection on New Product Design - Hadaina, Arsy Najwa; Jatiningsih, Dyah Ekaari Sekar (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the effect of cost information and process selection on total costs in sustainable new product design. This study uses an experimental design with the research objective to evaluate how these two variables contribute to cost efficiency and greener product innovation. To achieve this goal, students of the Accounting Study Program from the Faculty of Economics and Business, Universitas Muhammadiyah Yogyakarta as a substitute for professional designers in the development of new products were asked to fill out a questionnaire to evaluate their design choices, consider the sustainability aspects, and identify the challenges they faced during the process. The interaction effect was also assessed to review the correlation effect of these factors on sustainable product design, with the results showing that the interaction effect of the two variables has a significant impact on the total cost, supporting the hypothesis that the combination of these two factors is important in creating cost efficiency in sustainable product development